2019
DOI: 10.1016/j.jaci.2018.12.835
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Early Peanut Introduction Guidelines Among Pediatricians

Abstract: RATIONALE: To evaluate the safety of sublingual immunotherapy (SLIT) for peanut allergy using commercially prepared peanut cream. METHODS: We enrolled children aged <15 years who were diagnosed with peanut allergy by an open oral food challenge (OFC) and who agreed to undergo peanut SLIT. Doses of peanut protein from commercially prepared peanut cream were gradually increased from 13.8 mg/day to 4600 mg/day over the study period. We evaluated adverse events during SLIT and changes in maximum tolerated OFC dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…More recent studies involving medical record review of infants at the 4 to 6–month well-child visits have also suggested low rates of guideline adherence. 11 , 16 In a review of 312 infant well-child visits in a Chicago clinic, pediatricians were fully adherent to the guidelines for only 14% of infants, regardless of risk level. 11 Tapke et al 16 indicated that early peanut introduction was discussed in 3.3% of the 4 to 6–month well-child visits of infants with high risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies involving medical record review of infants at the 4 to 6–month well-child visits have also suggested low rates of guideline adherence. 11 , 16 In a review of 312 infant well-child visits in a Chicago clinic, pediatricians were fully adherent to the guidelines for only 14% of infants, regardless of risk level. 11 Tapke et al 16 indicated that early peanut introduction was discussed in 3.3% of the 4 to 6–month well-child visits of infants with high risk.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 16 In a review of 312 infant well-child visits in a Chicago clinic, pediatricians were fully adherent to the guidelines for only 14% of infants, regardless of risk level. 11 Tapke et al 16 indicated that early peanut introduction was discussed in 3.3% of the 4 to 6–month well-child visits of infants with high risk. These data raise the possibility that despite their knowledge of and willingness to adhere to the guidelines, pediatricians may encounter practical obstacles that decrease implementation rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the new guidelines, the rates of early peanut introduction remain low [20][21][22][23]. The recommendation for testing high-risk infants prior to early introduction created confusion [21,24], high cost [25], and logistical challenges [21,24,25].…”
Section: Introductionmentioning
confidence: 99%